Development of Surface Plasmon Resonance (SPR) Device as Biosensor Transducer - Hastito, Fadli; Juliastuti, Endang; Yuliarto , Brian (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
This study developed a simple and cost-effective laboratory-scale Surface Plasmon Resonance (SPR) device called β SPR. SPR is a sensitive, real-time, and non-labeling technique widely used to detect the concentration and quality of solutions. However, the very high price of commercial SPR devices is a barrier, so a portable and affordable version was developed. The β SPR device uses a Kretschmann configuration with a 670 nm laser, a polarizer, and a modified Porro BA4010 prism for a simpler and more efficient optical configuration. A thin gold film ( 50 nm) is placed on the prism using immersion oil, and the test solution is flowed through a flow cell. The laser is fired at a 90° angle to induce p-polarized waves that trigger surface plasmon resonance. This phenomenon decreases the light reflectance, forming a dip curve used for analysis. The device was tested using glucose solution (0.05–0.27 M) and compared with a commercial SPR device (α SPR). The results show a shift in the angle with increasing concentration. The highest error was 6.53% at 0.05 M, and the lowest was 0.94% at 0.27 M. The β SPR sensitivity was recorded at 4.41⁰/M, showing promising performance for cost-effective biosensor applications.